Development of children's hymenoptera venom allergy quality of life scale (CHVAQoLS). Issue 1 (1st August 2013) - Cichocka‐Jarosz, Ewa; Brzyski, Piotr; Tobiasz‐Adamczyk, Beata; Lis, Grzegorz; Pietrzyk, Jacek J
Abstract: Background: Venom allergy is a rare but life‐threatening disease and may have a considerable impact on the health‐related quality of life (HRQoL) of patients, especially children. This paper presents development of the HRQoL scale for children and adolescents with Hymenoptera venom allergy (HVA). Methods: The study sample consisted of 71 children, born between 1992 and 2000, who presented with a history of insect sting reaction when referred for consultation in the allergy center of Polish‐American Children's Hospital, Krakow, Poland, during the period from 2000 to 2010. The initial pool of 60 items ‐ divided into 6 domains ‐ was prepared. The items with intercorrelations higher than 0.7 were removed from each domain and then principal component analysis was conducted for each domain separately, to provide a one‐dimensional subscale for each domain. Reliability of the subscales was assessed using Cronbach alpha coefficient in terms of Classical Test Theory and with rho coefficient in terms of Item Response Theory. The multidimensionality of the scale was tested using multi‐trait scaling. Results: Three to four items from each domain were subsequently selected to constitute six subscales. Rho coefficients for all the subscales reached 0.8, similar results were achieved with the Cronbach alpha coefficients. Multi‐trait method showed that the majority of the items indicated stronger correlations with their own subscales than with other subscales, which proves that our constructed subscales measure different dimensions of HRQoL. Conclusions: The presented scale comprises high validity and reliability subscales measuring six dimensions of HRQoL related to Hymenoptera venom allergy in children and adolescents. Such information may be useful in everyday clinical practice.